EFEKTIFITAS PENYELENGGARAN DAN PENGELOLAAN DANA PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT (PNPM) MANDIRI PERKOTAAN DI KECAMATAN ILIR TIMUR II PALEMBANG - Welly Welly (Universitas Indo Global Mandiri)
The aim of this research was to know the effectiveness of implementation and financial management of empowerment national program of independent urban. The type of this research was descriptive by using primer and secondary data. The technique of collecting data was interview and documentation with qualitatif data analysis. The result of the study showed that was the effectiveness of the implementation empowerment national program of independent urban to Lembaga Keswadayaan Masyarakat (LKM) Usaha Bersama , Ampera and Duku at district of Ilir Timur II of Palembang was effective, although there were still lack of implementation, like LKM Usaha Bersama is the most effective viewed from indicator of source and target approach that run well. The lack of LKM Usaha Bersama, Ampera and Duku were approach processing, where implementation process and time implementation program were not reached yet because of the lateness of fund. For the effectiveness financial management of PNPM, only LKM Usaha Bersama that followed the direction of financial management viewed by accountability indicator and financial management transparancy, where as for LKM Duku and Ampera were not maximal yet viewed by activity report to society. Keywords: Effectiveness, Accountability, Transparancy.